Listen to me! : the voices of pupils with emotional and behavioural difficulties (EBD) - Wise, Susan (Lucky Duck Pub., 2000)
The author uses research into the experiences of young people disaffected with school to provide a fascinating insight into the feelings and views of those who are hard to motivate. What we learn is that we might not like or agree with what we hear, but if we are to include these young people in our schools then we must listen to them.- Resumé vydavatel
Keywords: problémové děti; školství -- Velká Británie; problem children; education -- Great Britain; elektronické knihy; monografie; electronic books; monographs